Crown of souls [large type] - Kendig, Ronie (Kendig, Ronie. Tox files, 2017)
"Tox battles a growing darkness within himself as he and his team are forced into another deadly encounter with antiquity when a rogue Special Forces operator attempts to use a mysterious artifact to seek vengeance on those responsible for the orders that got his men killed."--